Peran Kebijakan Perlindungan Ketenagakerjaan Dalam Meningkatkan Kesejahteraan Pekerja - Nikmah Dalimunthe; Ariyadi Ariyadi; Agung Setia; Dwi Nur Annisa; Indah Khuzaimah; Dwi Indah Pertiwi; Egi Fadilah Saragih; Nadiah Rizki Nasution; Irfan Iskandar (Jurnal Manajemen Riset Inovasi, 2023)
Given the wage disparity and perceived injustice experienced by both permanent and contract workers, it is necessary to conduct a study on legal protection regarding wages for the well-being of laborers. Therefore, this research aims to examine the role of labor protection policies, including social security for workers, fair wages, and the protection of labor rights, in promoting labor welfare. This study utilizes a qualitative method, which involves describing data and organizing it into various sentences. Additionally, a descriptive method is employed, where data is derived from words, sentences, images, and information from various books, journals, and other scholarly works that serve as references for labor protection and worker well-being. The findings of the discussion indicate that labor protection in the form of social security, fair wages, and labor rights plays a significant role in improving labor welfare.